System for collecting, analyzing and visualizing data about devices in the Internet - Sh. R. Davlatov; P. V. Kuchynski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
This article describes the system for collecting, analyzing and visualizing of technical information about devices connected to the Internet based on the Censys platform. It was developed using Python programming language and it's intended for primary data analysis. The system can be used by security administrators to prevent potential threats in automated systems. This project was tested on the example of information about devices serving the most popular Internet resources in Belarus.